2017
DOI: 10.1371/journal.pone.0169404
|View full text |Cite
|
Sign up to set email alerts
|

Role of BmDredd during Apoptosis of Silk Gland in Silkworm, Bombyx mori

Abstract: Silk glands (SGs) undergo massive apoptosis driven degeneration during the larval-pupal transformation. To better understand this event on molecular level, we investigated the expression of apoptosis-related genes across the developmental transition period that spans day 4 in the fifth instar Bombyx mori larvae to day 2 pupae. Increases in the expression of BmDredd (an initiator caspase homolog) closely followed the highest BmEcR expression and resembled the expression trend of BmIcE. Simultaneously, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…It undergoes a dramatic degeneration after spinning (Matsuura, Morimoto, Nagata, & Tashiro, ). Recently, many studies have elucidated the mechanism from the mRNA levels, some important genes such as Bmatg , BmDredd , and BmEcR were also found regulating the degeneration of the silkgland (R. T. Chen et al, ; R. Chen et al ; Huang et al, ; Zhang et al, , ). Many studies have demonstrated that some mRNAs could induce apoptosis in silkworm cells, but this was not clear enough to reveal why larva‐specific tissues degenerate while others not during the metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It undergoes a dramatic degeneration after spinning (Matsuura, Morimoto, Nagata, & Tashiro, ). Recently, many studies have elucidated the mechanism from the mRNA levels, some important genes such as Bmatg , BmDredd , and BmEcR were also found regulating the degeneration of the silkgland (R. T. Chen et al, ; R. Chen et al ; Huang et al, ; Zhang et al, , ). Many studies have demonstrated that some mRNAs could induce apoptosis in silkworm cells, but this was not clear enough to reveal why larva‐specific tissues degenerate while others not during the metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some apoptosis‐related genes have been investigated in the silkworm silk gland or in silkworm ovary cells (R. T. Chen et al, ; Huang et al, ; Yi et al, ; Zhang et al, ; Zhang, Zhao, Qiao, Pan, & Lu, ). However, except for the function of Bm Dredd in the silk gland (R. Chen et al, ), few papers reported the functions of inhibiting or inducing apoptosis on the individual level of the silkworm. Therefore, the mechanisms of silk gland degeneration still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As an important economic insect, the value of B. mori is dependent on the functionality of its silk gland, a specialized organ that synthesizes silk proteins in the silkworm (Chen et al., ). Fibroin is the most significant component of silk fiber, accounting for 70–80% of the total fiber (Zhong et al., ), which mainly synthesized in PSG of B. mori and then secreted by ASG and MSG (Li et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…All insect IMDs may be cleaved in vivo in the same way as DmIMD. PxIMD is likely to be cleaved in vivo by PxDREDD (Chen et al., ; Chen et al., ; Wang et al., ). Two IMD homologs were identified from Chinese white shrimp Fenneropenaeus chinensis and red swamp crayfish Procambarus clarkii (Feng, Wang, Wen, & Li, ; Lan et al., ).…”
Section: Discussionmentioning
confidence: 99%